2012
DOI: 10.1371/journal.pone.0049226
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal Nanofiber Textiles Based on Photosensitized Production of Singlet Oxygen

Abstract: Novel biomaterials based on hydrophilic polycaprolactone and polyurethane (Tecophilic®) nanofibers with an encapsulated 5,10,5,20-tetraphenylporphyrin photosensitizer were prepared by electrospinning. The doped nanofiber textiles efficiently photo-generate O2(1Δg), which oxidize external chemical and biological substrates/targets. Strong photo-virucidal effects toward non-enveloped polyomaviruses and enveloped baculoviruses were observed on the surface of these textiles. The photo-virucidal effect was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 44 publications
0
44
0
2
Order By: Relevance
“…The results showed that baculovirus is more resistant to photoinactivation than the polyomavirus. The textiles were also tested after a year of storage at room temperature in the dark with the same results which indicate their long-term photovirucidal efficiency [60].…”
Section: Porphyrin-embedded Fabricmentioning
confidence: 65%
See 3 more Smart Citations
“…The results showed that baculovirus is more resistant to photoinactivation than the polyomavirus. The textiles were also tested after a year of storage at room temperature in the dark with the same results which indicate their long-term photovirucidal efficiency [60].…”
Section: Porphyrin-embedded Fabricmentioning
confidence: 65%
“…No [47] No [50,52,69] On filter paper [82] On cotton fabric [86,108] On polysilsesquioxane plastic films [61] On cotton fabric [87] On azide-modified cellulose nanocrystals [43,75] On chloroacetyl cellulose ester chlorides [78] On cellulose laurate esters plastic films [79] No [71] No [93] No [49,71,93,110] and Tri-Py + -Me-PF on silica coated Fe3O4 nanoparticles [70] and also on CoFe2O4 nanoparticles [111] No [81] No [105] No [36,37,71,74,81,105]; Tetra-Py + -Me was entrapped into microporous silica gels [88] and into three alkylene-bridged polysilsesquioxanes [89] On optically transparent indium tin oxide electrodes [63] On chitosan membranes [72] Pd(II) TetraTPPCO2H On a polyurethane matrix [83] No [105] In hydrophilic polycaprolactone and polyurethane (TecophilicH) nanofibers [60]; on electrospun polymeric nanofiber materials polyurethane Larithane TM , polystyrene, polycaprolactone, and polyamide 6 [76]; into three alkylene-bridged polysilsesquioxanes [89]; and in a silica-gel supported antimony porphyrin complex SbTPP [97,98] No [44,…”
Section: Porphyrinmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of wipes coated with antimicrobials may allow combined cleaning and disinfection of surfaces and prevent crosscontamination via the cleaning cloth if the pathogen is inactivated efficiently in the cloth. Cloths that incorporate antimicrobials such as light-activated polymers or copper-based biocides have been shown to be efficient in inactivating pathogens (36)(37)(38)(39)(40).…”
mentioning
confidence: 99%